INFLUENCE OF POLYMER MATRICES ON THE ELECTRICAL PROPERTIES OF COMPOSITE COATINGS - СВІСТІЛЬНІК, Р. Ф.; ФЕДОРІВ, Т. Р. (Technologies and Engineering, 2024)
Purpose. This study aims to determine how the polymer matrix affects the electrical properties of composite coatings containing conductive carbon filler. Methodology. The specific surface and volumetric electrical resistivity of the coatings were measured using a four-electrode cell and the Kelvin method. The dynamic viscosity of the polymer matrix solution was assessed with a VEVOR NDJ-9S rotational viscometer. The dry residue of the composite coating solution was determined by the weight method. Findings. The study reveals the significant impact of polymer matrices on the electrical properties of composite polymer coatings. Notably, coatings based on nitrocellulose (NC) exhibit the lowest surface and bulk electrical resistance, likely due to the highly polar nitro groups in the NC matrix. Conversely, coatings with a Bakelite resin (BR) matrix show the highest resistance. For coatings combining a polyvinyl butyral (PVB) matrix with 5% and 10% Bakelite resin (BS), lower resistance is observed at 5% BS, with an increase in resistance at 10% BS, compared to coatings solely based on PVB. The selection of a suitable polymer matrix for electrically conductive composite coatings depends on specific properties like strength, chemical resistance, and fire resistance. Originality. This research uniquely identifies the impact of different polymer matrices on the electrical resistivity of composite coatings Practical value. The findings will aid in selecting the appropriate polymer matrix for flexible heating elements, tailored to their specific applications.